Fire Promotes Arsenic Mobilization and Rapid Arsenic(III) Formation in Soil via Thermal Alteration of Arsenic-Bearing Iron Oxides - Johnston, Scott G.; Karimian, Niloofar; Burton, Edward D. (Frontiers in Earth Science, 2019)
Arsenic in oxic surface soils readily associates with Fe(III) oxide minerals such as ferrihydrite and goethite, predominantly as As(V). Fires are a common feature in many landscapes, creating high-temperature soil conditions which drive thermal transformation of these As(V)-bearing minerals. However, it is unknown whether fire-induced transformation of ferrihydrite and goethite can alter the mobility of As, or alter As(V) speciation (e.g. via pyrolysis induced electron-transfer generating the more mobile and toxic inorganic As(III) species). Here, we subject an organic-rich soil (~15% organic C) mixed (4:1) with As(V)-bearing ferrihydrite and goethite (total As of 2.8-3.8 mol g-1), to various temperatures (200-800oC) and heating durations (5-120 min) and examine the consequences for As and Fe via X-ray absorption spectroscopy, X-ray diffraction, 57Fe Mössbauer spectroscopy and selective extracts. We show that heating transformed both ferrihydrite and goethite to mainly maghemite at temperatures >400oC and tended to increase exchangeable surface-complexed As (AsEx) in ferrihydrite yet decrease AsEx in goethite. We demonstrate for the first time that ferrihydrite and goethite-bound As(V) can be rapidly reduced to As(III) during heating of organic-rich soil. Electrons were readily transferred to both Fe(III) and As(V), with reduction of As(V) to As(III) peaking at intermediate temperatures and time periods (maxima of ~88% for ferrihydrite; ~80% for goethite). Although As(III) formation was fast (within 5-10 min at temperatures >400oC), it was followed by partial re-oxidation to As(V) at higher temperatures and longer time intervals. Additionally, combusted As-bearing ferrihydrite and goethite soil-mixtures display greatly enhanced (2-3 orders of magnitude) mobilisation of inorganic As(III)aq species upon re-wetting with water. The magnitude of As(III)aq mobilisation was positively correlated with solid-phase As(III) formation and was greater for goethite than ferrihydrite. These findings challenge the current prevailing view that As(V) reduction to As(III) in soil is mainly limited to waterlogged conditions and suggest that moderate-temperature fires of short duration in oxic soils, may generate considerable labile As(III) species and cause a pulse of As(III)aq mobilisation following initial re-wetting. Further research is warranted to examine the consequences for arsenic cycling in fire-prone natural landscapes and agricultural systems which involve controlled-burn practices.